2011
DOI: 10.1007/s00248-010-9789-0
|View full text |Cite
|
Sign up to set email alerts
|

Plumage Bacterial Assemblages in a Breeding Wild Passerine: Relationships with Ecological Factors and Body Condition

Abstract: Microorganisms have been shown to play an important role in shaping the life histories of animals, and it has recently been suggested that feather-degrading bacteria influence the trade-off between parental effort and self-preening behavior in birds. We studied a wild breeding population of great tits (Parus major) to explore habitat-, seasonal-, and sex-related variation in feather-degrading and free-living bacteria inhabiting the birds' yellow ventral feathers and to investigate associations with body condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 50 publications
3
66
0
Order By: Relevance
“…Given bacterial:fungal competitive interactions, these two findings are unlikely to be independent of one another. Sex-based differences in feather bacterial OTU richness have been observed previously (Saag et al 2011) but in reverse with females supporting higher OTU richness.…”
Section: Microbial Otu Richness and Baseline Communitiesmentioning
confidence: 83%
See 2 more Smart Citations
“…Given bacterial:fungal competitive interactions, these two findings are unlikely to be independent of one another. Sex-based differences in feather bacterial OTU richness have been observed previously (Saag et al 2011) but in reverse with females supporting higher OTU richness.…”
Section: Microbial Otu Richness and Baseline Communitiesmentioning
confidence: 83%
“…This is despite adult birds being both a source of microbes and the recipient of microbes originating from the nesting environment that could have a potential role in shaping avian life histories (Stewart and Rambo 2000). In one of the only studies on this topic, Saag et al (2011) showed plumage bacterial load of adult female great tits was higher in the nest-building period than when females were provisioning for chicks, possibly due to increased contact with nesting material. Additional support for this was offered by a follow-up study (Kilgas et al 2012), which showed that plumage bacterial load increased during the nest-building process.…”
Section: Vergangene Untersuchungen Waren Konzentriert Auf Unterschiedmentioning
confidence: 99%
See 1 more Smart Citation
“…following lucas et al (2003a), we separated the two types of bacteria in the laboratory and, to determine their density, counted free-living and attached bacteria directly with a flow-cytometry machine (bD lSR II). for tagging we used the DNA-binding dye SybR green (for further details see Saag et al 2011). bacterial densities are expressed per feather.…”
Section: Density Of Free-living and Attached Bacteria On Feathersmentioning
confidence: 99%
“…On the basis of earlier findings that higher chroma (Senar et al 2008, broggi andSenar 2009) and lower density of attached bacteria (Saag et al 2011) signal better individual quality of female great Tits, we predicted a negative association between chroma and bacterial density.…”
Section: Introductionmentioning
confidence: 99%